The relationship between economic growth and government behaviour in Malaysia / Hanani Ahmad Fuad, Hapiza Omar dan Nor Hidayah Harun - Ahmad Fuad, Hanani; Omar, Hapiza; Harun, Nor Hidayah (2012)
Malaysia experienced an increasing GDP over years since independence. This high growth is said to be influenced by structured and excellent government economic policy. With an increasing government spending and debt, this government behaviour is expected to promote Malaysian growth. However, in previous studies, this government behaviour is not significant; therefore, it is an interesting issue to be discussed. This study examined the relationship between economic growth and government behaviour in Malaysia for the period of 1970 until 2010. It examined the long run relationship between economic growth and government behaviour variables, including government spending, government revenue and public debt, using Cointegration test. It also investigated the causation between the variables using Granger causality test. The result showed that there is no long run relation between economic growth and government spending, but there is significant relation with the other two variables. However, Granger causality found that economic growth Granger causes government spending and revenue in the short run and also government revenue causes the spending.